Intracervical Lidocaine Block is more Effective for Pain Management of Curettage in Incomplete Abortion - Saranga, Oktovianus (Indonesian Journal of Obstetrics and Gynecology, 2014)
Objective: To compare the effects of Intra cervical and paracervical block with 1% lidocaine for pain management in curettage of incomplete abortion. Method: This study is a prospective study with Randomized Control Trial approach. The samples were 52 pregnant women with gestational age of less than 20 weeks, which diagnosed as having an incomplete abortion and a procedure using any local anesthetic technique. T test was used to calculate the mean VAS score and standard deviation for each group. Fisher Exact test was used to assess the relationship between variable characteristics and the local anesthetic technique. Result: The use of local anesthesia using intra cervical block technique for pain management in incomplete abortion with curettage proved to be more effective in lowering degree of pain than paracervical block techniques. Conclusion: Intracervical block technique as a local anesthetic technique is simpler and relatively safer than paracervical block. This technique can be used extensively in Department of Obstetrics and Gynecology Medical Faculty, Hasanuddin University for pain management in curettage. [Indones J Obstet Gynecol 2014; 2-1: 13-17] Keywords: pain, Intracervical anesthesia, paracervical anesthesia, Visual Analogue Scale (VAS)